The Electronic Commerce and Online consumption of undergraduate students of a Public University in the interior of the Northeast (Research, Society and Development, 2019)
We aim to study the online consumption characteristics of the students of the undergraduate courses in Administration and Accounting Sciences of the Sousa Campus of the Federal University of Campina Grande. Connectivity through the devices and the need for contact between people are part of the modern world, taking as an example e-commerce and constant growth. With the model of doing business through the internet, came the changes in people in the form of consuming goods and services, thus creating new consumption habits. In this context, the study has as study the online consumption characteristics of the students of the undergraduate courses in Administration and Accounting Sciences of the Sousa Campus of the Federal University of Campina Grande. The research is classified as quantitative, descriptive, explanatory and field research, using a questionnaire in interviews with the target audience of the study. With the obtained data, it was possible to trace the demographic profile of the students studied, characterized by a predominant age between 18 and 24 years, due to the application of the questionnaire to university students. It was verified that the internet is the main source of information of the interviewees in relation to the acquisition of products and services. Thus, it was possible to verify that the consumer characteristics of the respondents are similar to the profile of the national consumer, in particular the familiarization with the online shopping environment. The results of the survey served to confirm the reality that consumers have on the Internet an ally when it comes to informing about possible purchases.